Evaluation of the Level of Physical Damage Due to Erosion in Post-Sand Mining Land Using the Universal Soil Loss Equation (USLE) Method - Novalisae Novalisae; Noveriady Noveriady; I Putu Putrawiyanta; Ferdinandus Ferdinandus; Yulius Kahanjak; Grace Any Pasaribu (G-Tech: Jurnal Teknologi Terapan, 2026)
Sand mining activities at Km. 29 in Bukit Batu District, Palangka Raya City, have caused significant physical land damage. This study quantifies erosion rates in former sand mining areas using the Universal Soil Loss Equation (USLE) through field surveys and laboratory analysis. Soil samples were collected purposively from four locations (Kolong 1 TL, Kolong 2 TL, Kolong 1 BD, Kolong 2 BD) at 0-20 cm depth with three replications. Results showed erosion rates ranging from 0.54 to 2.52 tons/ha/year, classified as “very low” according to standard erosion hazard categories. However, in post-mining contexts with initial degradation, these rates indicate serious land vulnerability. The dominant factors influencing erosion were high rainfall erosivity (R=998.45 MJ.mm/ha/hr/year), minimal vegetation cover (C=0.8), and the absence of conservation practices (P=1), whereas soil erodibility was inherently very low (K=0.005-0.014). Although numerically classified as very low, the former sand mining land requires immediate conservation intervention. Practical implications emphasize integrated conservation through vegetative approaches (fast-growing cover crops) and mechanical methods (gulud terraces and rorak), focusing on modifying the conservation practice factor (P) as the most easily intervenable variable to prevent increased erosion and restore land conditions.